Microsatellite Genotyping to Distinguish Somatic β-HCG Secreting Carcinoma from Epithelioid Trophoblastic Tumor - Mary Anne Brett; Monalisa Sur; Dean Daya; Jefferson Terry; Alice Lytwyn (Hindawi Limited, 2015)
Objective. Morphologically, β-HCG secreting somatic carcinoma can be difficult to distinguish from epithelioid trophoblastic tumors (ETT). However, their distinction is critical due to their potentially differing prognoses and choice of chemotherapy. Presence of biparental alleles in ETT can be identified with molecular testing. We describe a patient who presented with metastatic carcinoma and elevated serum β-HCG and contrast this to an ETT in another patient. Data and Results. A 32-year-old female with recent possible miscarriage presented with pulmonary emboli and was found to have an increased serum β-HCG, a retroduodenal mass, and multiple nodules in her lungs, liver, and para-aortic lymph nodes. Biopsy showed a β-HCG and p63 positive epithelioid neoplasm with otherwise noncontributory immunohistochemistry. Molecular testing for biparental alleles in repeated length polymorphisms was negative, consistent with somatic origin. The second patient was a 35-year-old pregnant female with increased serum β-HCG and a uterine epithelioid tumor positive for β-HCG. Clinical and pathologic findings were characteristic of ETT and molecular testing was not required. These 2 cases illustrate that β-HCG secreting tumors of different etiologies may have similar appearances, and when clinical and/or IHC findings are inconclusive, molecular testing may be useful.